Perioperative intrapelvic hyaluronate application as prophylaxis against complications following rectal anastomotic dehiscence: An experimental study - Paral, Jiri; Odlozilova, Sarka; Sirovy, Miroslav; Zajak, Jan; Kotek, Jiri; Lochman, Petr (Asian journal of surgery, 2022)
PURPOSE: The aim of this experimental study was to test the method of prevention of postoperative complications, especially infectious, in partial dehiscence following stapler anastomosis in rectal surgeries. METHODS: The method includes the application of a hyaluronic acid-based gel in combination with triclosan, which has antibacterial properties. The gel was applied to the space around the rectum with an artificial, precisely defined dehiscence so that the dehiscence was separated from the rest of pelvis and the peritoneal cavity to avoid the spread of infection. The study included 30 female pigs. The rectosigmoid colon was mobilized and transected completely. Anastomosis was constructed with circular staplers. A perforator was then used to create precisely defined artificial dehiscence. Subsequently the lesser pelvis was filled with hyaluronic gel such that the site of artificial dehiscence was covered completely. RESULTS: All animals survived for 14 days until the second-look revision with no signs of failure in the anastomosis healing, local inflammation, and sepsis or postoperative complications, such as chills, refusal of liquid or feed, abdominal distension, and bowel obstruction. CONCLUSION: Hyaluronic acid applied as a precursor solution around the rectal anastomosis fills the lesser pelvis perfectly. It prevents the leakage of intestinal contents in the lesser pelvis. Triclosan as an antibacterial substance prevents the spread of inflammation in the pelvis or even in the abdominal cavity.
Keywords: netěsnost anastomózy; anastomóza chirurgická; Humans; Pelvis; Female; Anastomosis, Surgical; Rectum; triclosan; Inflammation; lidé; antibakteriální látky; zvířata; pánev; zánět; nádory rekta; Hyaluronic acid; Swine; Postoperative Complications; pooperační komplikace; ženské pohlaví; Rectal Neoplasms; Anti-Bacterial Agents; kyselina hyaluronová; Anastomotic Leak; Dehiscence; Rectal surgery; Animals; Triclosan; rektum; Hyaluronic Acid; prasata